2007
DOI: 10.1111/j.1741-4520.2006.00135.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal vitamin B12deficiency affects spermatogenesis at the embryonic and immature stages in rats

Abstract: To evaluate the role of cobalamin (Cbl) on spermatogenesis, the effect of dietary vitamin B(12) deficiency on early spermatogenesis was histologically investigated in male fetuses and newborns in the first filial generation (F(1) males) of rats. There was no difference in the number of gonocytes and supporting cells of Sertoli in the gonad in male fetuses on day 16 of gestation and in the testes in F(1) males at 0 days of age between vitamin B(12)-deficient (VB12-D) and vitamin B(12)-supplemented (VB12-S) grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 18 publications
0
22
0
1
Order By: Relevance
“…The correlation between vitamin B12 and reproductive performance in mammals has been demonstrated in several studies. For example, in rats, the deficiency of vitamin B12 has been linked to testicular atrophic changes and defects in spermatogenesis (Watanabe et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…The correlation between vitamin B12 and reproductive performance in mammals has been demonstrated in several studies. For example, in rats, the deficiency of vitamin B12 has been linked to testicular atrophic changes and defects in spermatogenesis (Watanabe et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Because these conditions were reversible (after weaning at 21 days of age), Watanabe et al (2007) posited that cobalamin may be a requisite constituent for meiosis of spermatogenesis. Of interest is the concept that dietary vitamin B 12 deficiency during pregnancy may induce irreversible damage in the germ cells of embryos and affect the maturation of spermatozoa (Watanabe et al, 2003), a theory with considerable ramifications.…”
Section: Discussionmentioning
confidence: 98%
“…It has been suggested that dietary vitamin B 12 deficiency affects both developing (damage to germ cells and sperm maturation) and growing (lower sperm count and morphology, but not motility) male rats [47]. In 2007, Watanabe et al [47] showed that vitamin B 12 deficiency during gestation and lactation phases affected the germ cells and led to spermatocyte destruction in the F1 male rats, which consequently reduced the quantity of the produced sperm. …”
Section: Effect Of Vitamin B12 On Sperm Parametersmentioning
confidence: 99%